Numerical simulation of coupled aerothermal vibrations of the turbine blade - Быков, Юрий Адольфович; Гнесин, Виталий Исаевич (Eastern-European Journal of Enterprise Technologies, 2011)
In the paper mathematic model and numerical method of simulation of coupled aerothermoelastic vibrations of turbomachine blade is presented. The results of the simulation of aerothermoelastic vibrations of turbine cooled blade are demonstrated